Association of Body Weight Variability With Progression of Coronary Artery Calcification in Patients With Predialysis Chronic Kidney Disease - Suh, Sang Heon; Oh, Tae Ryom; Choi, Hong Sang; Kim, Chang Seong; Bae, Eun Hui; Oh, Kook-Hwan; Lee, Kyu-Beck; Han, Seung Hyeok; Sung, Suah; Ma, Seong Kwon; Kim, Soo Wan (Frontiers in Cardiovascular Medicine, 2022)
Background We investigated whether high body weight variability (BWV) is associated with a higher prevalence of coronary artery calcification (CAC) or more rapid progression of CAC in patients with predialysis chronic kidney disease (CKD). Methods A total of 1,162 subjects from a nationwide prospective cohort of predialysis CKD were analyzed. The subjects were divided into the tertile (T1, T2, and T3) by BWV. CAC was assessed at the baseline and a 4-year follow-up by CT scan. Rapid progression of coronary artery calcification was defined as an increase in coronary artery calcium score (CACS) more than 200 Agatston units during a 4-year follow-up. Results One-way ANOVA revealed that CACS change during the follow-up period is significantly higher in the subjects with high BWV, although CACS at the baseline and 4-year follow-up was not different among the tertile groups by BWV. Logistic regression analysis revealed that compared to low BWV (T1), both moderate (T2, adjusted odds ratio (OR) 2.118, 95% CI 1.075–4.175) and high (T3, adjusted OR 2.602, 95% CI 1.304–5.191) BWV was associated with significantly increased risk of rapid progression of CAC. Importantly, the association between BWV and progression of CAC remained robust even among the subjects without significant BW gain or loss during follow-up periods (T2, adjusted OR 2.007, 95% CI 1.011–3.984; T3, adjusted OR 2.054, 95% CI 1.003–4.207). Conclusion High BWV is independently associated with rapid progression of CAC in patients with predialysis CKD.